A mundividência de Diogo Pires à luz da colectânea poética dos Xenia - Andrade, António Manuel Lopes
By the end of his life, Diogo Pires has published an extensive poetic compilation in Venice entitled Cato Minor siue Disticha Moralia. In this study, we seek to analyse one of the widest collections included in this work – Xenia ad Ianum Claudium Ciuem Rhacusanum –, a large assemblage of distichs inspired by the eponymous book incorporated in Marcial’s Epigrammata. If the Xenia (and also the Apophoreta) by the Bilbilis poet offer invaluable insight into Roman daily life in the 1st century, it is also undeniable that the book by the Évora poet provides us with a vivid recollection of his personal world, revealing his inclinations and most remote memories. Diogo Pires handles a broad range of themes in an ingenious and concise manner, by resorting to plain elegiac distichs that illustrate the felicitous interweaving of two places and times: Classical Antiquity and Renaissance. Keywords: Diogo Pires, Martial, Neolatin poetry, Renaissance Humanism